Engineering Thermofluids Thermodynamics, Fluid Mechanics, and Heat Transfer - Massoud, Mahmoud; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
The "Engineering Thermofluids" is a unique textbook, which brings the three pillars of thermal sciences; thermodynamics, fluid mechanics, and heat transfer under one umbrella. These three distinct, yet intertwined subjects are treated in an integrated manner. The primary audiences for this book are senior undergraduate, graduate, and practicing engineers in the fields of aeronautical, chemical industrial, mechanical, and nuclear engineering. Topics are discussed in detail while still using a simple and easy to follow approach. Numerous walk-through examples are solved and illustrations are provided to guide the reader through more subtle topics. Each chapter starts with a section for the introduction of various terminologies used. The chapter on thermodynamics covers the first law, the second law, the power cycles, and the mixture of gases. The chapter on fluid mechanics covers both steady-state and transient single phase-flow as well as two-phase flow. The chapter on heat transfer covers conduction, convection, radiation, boiling, and condensation. These chapters are followed by the chapter on applications of the engineering thermofluid, which covers the design and operations of various heat exchangers, turbomachines, and flowmeters. Many practical design problems are either solved or provided as homework. Practicing engineers will find this book a useful text to have around for the many practical problems and solutions, illustrations, definitions, methods, tables, and figures provided. The preference throughout the text is on obtaining analytical solutions of a closed form. Numerical solutions as well as experimental results are presented when analytical solutions cannot be found.
Introduction -- Thermodynamics, Fundamentals -- Thermodynamics, Power Cycles -- Thermodynamics, Mixtures -- Fluid Mechanics, Single-Phase Flow Fundamentals -- Fluid Mechanics, Flow of Incompressible Viscous Fluid -- Fluid Mechanics, Flow of Compressible Viscous Fluid -- Heat Transfer, Conduction -- Heat Transfer, Forced Convection -- Heat Transfer, Free Convection -- Heat Transfer, Thermal Radiation -- Two-Phase Flow and Heat Transfer, Two-Phase Flow Fundamentals -- Boiling -- Condensation -- Fundamentals of Heat Exchangers -- Fundamentals of Flow Measurement -- Fundamentals of Turbomachines -- Simulation of Thermofluid Systems -- Nuclear Heat Generation -- Engineering Mathematics, Fundamental -- Differential Equations -- Vector Algebra -- Linear Algebra -- Numerical Analysis.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Chemical engineering; Fluid mechanics; Energy systems; Energy; Engineering Thermodynamics, Heat and Mass Transfer; Industrial Chemistry/Chemical Engineering; Engineering Fluid Dynamics; Energy Systems; Energy, general